Impacts of climate, disturbance and topography on distribution of herbaceous cover in Southern California chaparral: Insights from a remote‐sensing method. Issue 4 (21st January 2018) - Park, Isaac W.; Hooper, Jennifer; Flegal, James M.; Jenerette, G. Darrel
Abstract: Aim: While chaparral communities have historically been considered resistant to invasion and type conversion into grasslands, interacting global changes such as increased drought and anthropogenic disturbance may have reduced this resistance. Existing monitoring methods are not well‐suited to evaluate the distribution of invasive herbs and grasses within chaparral at regional scales. In this study, we determine the extent of invasions by forbs and grasses into formerly chaparral vegetation and evaluate contributions of moisture, disturbance and anthropogenic activity and topography to the distribution of herbaceous cover throughout chaparral‐dominated communities. Location: The Angeles National Forest (ANF), California, USA. Methods: We developed a remote‐sensing method to estimate the distribution of herbaceous cover within chaparral by leveraging intra‐annual phenological differences in normalized difference vegetation index (NDVI) between herbaceous forbs and grasses and evergreen shrublands using Landsat remote‐sensing imagery. The distribution of herbaceous cover was then related to multiple spatially explicit variables describing individual and interactive effects of local moisture availability and anthropogenic disturbance. Results: Herbaceous cover represents approximately 31% of the ANF within the elevation range typically dominated by chaparral. Disturbance‐related and anthropogenic factors explained 17% of observed variation, while differences in moisture availability explained 47% of observed variation in herbaceous cover and were associated with increased invasive cover. Main conclusions: Landscapes historically dominated by chaparral may exhibit high degrees of herbaceous cover. While fire frequency and other anthropogenic disturbances are likely the primary catalyst for invasion of chaparral by herbaceous species, this study shows that moisture availability is a more important factor in determining which locations are successfully invaded. These results indicate that chaparral vulnerability to invasion in southern California may increase in the next century due to reduced precipitation associated with projected climate change.